Herpes simplex virus type 2 serological testing at a community court: Predictors of test acceptance and seropositivity among female defendants. (March 2013) - Roth, A M; Van Der Pol, B; Fortenberry, J D; Reece, M; Dodge, B; Certo, D; Zimet, G D
Despite the high prevalence of herpes simplex virus type 2 (HSV-2), testing for asymptomatic infections is uncommon. One population for whom targeted interventions may be prioritized include individuals involved with the correctional system. Here we describe the acceptability of a novel HSV-2 screening program, implemented in a court setting, as a possible intervention for corrections-involved women. Female defendants completed an interviewer administered survey assessing factors associated with uptake/refusal of free point-of-care HSV-2 serologic testing and HSV-2 seropositivity. Participants included 143 women, 18–62 years old (mean 32.85) with diverse ethnicities. The majority (65.7%) accepted testing and 62.4% tested HSV-2 seropositive. Factors independently associated with test acceptance included higher perceived susceptibility to genital herpes infection and not receiving a preventative health screen. Women who were seropositive tended to be older, Black, report having previous STI, and be arrested on a prostitution charge. Findings suggest point-of-care testing in a court setting is acceptable to women and can be implemented to improve case finding of STI.